Bondholders’ wealth effects in domestic and cross-border bank mergers - Ongena, Steven; Penas, María Fabiana (Journal of Financial Stability, 2009)
The recent credit crisis and the increased internationalization of the European banks have given the debate about the role of national regulators a renewed urgency. We therefore investigate the determinants of bondholders’ abnormal returns for both domestic and cross-border bank merger announcements that involve European acquirers for the period 1998–2002. We find that bondholders’ abnormal returns are higher for Domestic Mergers than cross-border mergers, in direct contrast to evidence from equity prices where no difference is found. Further investigations in which we control for the changes in market power for example suggest this result may be indicative of investors perceiving Domestic Mergers as increasing the probability of a government bailout in case of distress. Banks’ bondholders also experience higher abnormal returns when the country of the partner bank has stricter rules in relation to forbearance of prudential regulations than the own country, and when functional diversification between lending and fee/trading activities increases.